Development of indicators for family well-being in Malaysia - Noor, Noraini M.; Doshi-Gandhi, Anjli; Ishak, Ismahalil; Wok, Saodah (Springer, 2014)
This study was carried out to develop a set of indicators for measuring and reporting the state of family well-being in Malaysia, and subsequently, to produce an Index of Family Well-Being. To build the set of indicators, domains of family well-being and relevant indicators were identified from past studies. Focus group discussions with families, professional groups and NGOs helped to refine the indicators prior to the main study. Using a stratified random sampling design, 2,808 households were identified (a parent and a child aged at least 13 years), making a total sample of 5,616 respondents. Results indicated ten key indicators that can predict family well-being—resiliency, safety, savings, healthy lifestyle, time with family, work-family balance, importance of religion, number of bedrooms at home, debt and child care—supporting the notion of family well-being being multi-dimensional and interconnected. On the basis of the results, a model of family wellbeing was hypothesized. This model was used to guide the development of the Index of Family Well-being. Confirmatory factor analysis (CFA) was carried out to determine the fit of the model to data. Five domains of family well-being were identified—family relationships, economic situation, health and safety, community relationship and religion/spirituality. The Index of Family Well-Being was calculated using the equal weighting strategy to each of these five domains. This index showed that the current family wellbeing of Malaysians is relatively high at 7.95 (SD = 1.38) on a 0–10 Likert response format. The findings suggest that family well-being is multifaceted, made up not only of the immediate family relationships and health and safety of its members, but include having adequate income to meet the demands of a minimum standard of living. Currently, the Index that is developed is only in the form of a numerical value reflecting the state of family well-being, but in future, it can be used to track changes in the family from time to time.